2010
DOI: 10.1371/journal.ppat.1001245
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Intracellular Stages of Leishmania major Utilize Amino Sugars as a Major Carbon Source

Abstract: Intracellular parasites, such as Leishmania spp, must acquire suitable carbon sources from the host cell in order to replicate. Here we present evidence that intracellular amastigote stages of Leishmania exploit amino sugars in the phagolysosome of mammalian macrophages as a source of carbon and energy. L. major parasites are capable of using N-acetylglucosamine and glucosamine as primarily carbon sources and contain key enzymes required for conversion of these sugars to fructose-6-phosphate. The last step in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 45 publications
2
61
0
Order By: Relevance
“…A dependence on carbohydrate metabolism is supported by the presence of multiple sugar kinases in the Leishmania genomes (3) and may reflect the abundance of sugars in the sandfly mid-gut, particularly at later stages of infection when infected female sandflies feed on plants and sugar-rich honeydews (56). Intriguingly, hexose uptake and catabolism has also been shown to be essential for the survival and proliferation of L. mexicana and L. major amastigotes in the mammalian host (6,5) despite the fact that the macrophage phagolysosome appears to be a sugar-poor niche (39). Although the macrophage phagolysosome is expected to have relatively high levels of amino acids, amastigotes may still be limited in their capacity to salvage key amino acids such as glutamate, glutamine, and proline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dependence on carbohydrate metabolism is supported by the presence of multiple sugar kinases in the Leishmania genomes (3) and may reflect the abundance of sugars in the sandfly mid-gut, particularly at later stages of infection when infected female sandflies feed on plants and sugar-rich honeydews (56). Intriguingly, hexose uptake and catabolism has also been shown to be essential for the survival and proliferation of L. mexicana and L. major amastigotes in the mammalian host (6,5) despite the fact that the macrophage phagolysosome appears to be a sugar-poor niche (39). Although the macrophage phagolysosome is expected to have relatively high levels of amino acids, amastigotes may still be limited in their capacity to salvage key amino acids such as glutamate, glutamine, and proline.…”
Section: Discussionmentioning
confidence: 99%
“…GFP-expressing parasites were immobilized onto poly-L-lysine-coated coverslips and visualized by fluorescence microscopy (Zeiss Axioplan 2 microscope). Images were compiled in Photoshop (6).…”
Section: Expression Of Gfp-tagged Pep Carboxykinase In Promastigotes-mentioning
confidence: 99%
“…2). Another example of this type of inhibition was reported for Leishmania, in which the GlcNAc sensitivity of a gnd mutant lacking glucosamine deaminase was attributed to depletion of ATP (35). The inhibitory effect of GlcNAc on the Leishmania gnd mutant appears to be distinct from that seen for the C. albicans mutants because it could be overcome by adding alternative carbon sources, such as glycerol.…”
Section: -Pomentioning
confidence: 96%
“…Since GAPDH is also able to catalyze the reverse reaction from 3-phospho-D-glyceroyl phosphate into GAP in gluconeogenesis. The observation in this study that the L. donovani cGAPDH-null mutant had reduced infectivity in visceral organs suggests that cGAPDH could be involved in glycolysis and/or gluconeogenesis pathways when L. donovani resides as an amastigote in the macrophage phagolysosome, where the sugar levels are relatively low (47,51).…”
Section: Figmentioning
confidence: 72%
“…However, several studies have shown that glucose and/or amino sugars are required for the amastigote stage, though they might be mainly needed for the formation of glycoconjugates (46)(47)(48)(49). Leishmania amastigotes are able to utilize amino sugars in the phagolysosome of mammalian macrophages as a source of carbon and energy (47). Interestingly, gene deletion study of the gluconeogenic enzyme fructose-1,6-bisphosphatase (FBP) showed Leishmania also requires gluconeogenesis for its virulence (50).…”
Section: Figmentioning
confidence: 99%